PROSPEK PENGEMBANGAN BIOINSEKTISIDA NUCLEOPOLYHEDROVIRUS (NPV) UNTUK PENGENDALIAN / Prospect of Development of Nucleopolyhedrovirus (NPV) Bioinsecticide Against - Samsudin Samsudin (Puslitbang Perkebunan, 2016)
Chemical insecticides for estate crop pests control are ineffective, impractical, expensive, and causing environmental pollutions. The entomopathogenic virus (EPV) mainly the nucleopolyhedrovirus (NPV) can be developed as an effective, efficient, and environmentally friendly biopesticide. NPV can be survived in the field in the form of polyhedra and spread naturally through the vertical and horizontal transmission process. The infected larvae usually hang by pseudolegs to the leaves or entrees. Research to increase virulence, host spectrum and its persistence has been done to overcome some weaknesses of NPV if developed as biopesticide. Some NPV isolates that infect the estate crop pests and potential to be developed in Indonesia, among others: Spodoptera litura NPV (SlNPV), S. exigua NPV (SeNPV), Helicoverpa armigera NPV (HaNPV), Sethotosea asigna NPV (SaNPV), Hyposidra talaca NPV (HtNPV) and Maenas maculifascia NPV (MmNPV). Based on several advantages of NPV compared with the chemical insecticides, the development of NPV biopesticide for controlling estate crop pests in Indonesia has very good prospects.